IT LONG TAIL STRATEGY FOR SOFTWARE PACKAGE COMPANY - Andreas Winata; Lydia Theodore; Hoga Saragih (Bina Nusantara University, 2010)
Long Tail Strategy is a business strategy which explains that the total revenue from the sale of non-popular products may exceed the total income from popular products. This may happen since generally there is only a small number of popular products, which is in great demand, while there are many of the non-popular types which is sold in small amounts. This research aims to better understand the role of IT behind the success of the Long Tail strategy. Results show stages of how to develop IT strategy, including identification, analysis, determines on a strategy, until implementation. The results of this study will help software developers to plan IT strategy by implementing an accurate Long Tail Strategy.Keywords: Long Tail, IT Strategy, Services, Software Package